1987
DOI: 10.1007/bf01402373
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of intracranial mycotic aneurysm: Surgery or not

Abstract: Mycotic intracranial aneurysms are of infectious origin and, even nowadays, their treatment remains controversial with advocates for either surgical or medical treatment. We present the case of a 58-year-old patient who was admitted to the hospital with a left hemiparesis due to a large right parietal haematoma. An angiogram demonstrated a small vascular malformation localized on a distal parietal branch of the right Sylvian artery. The patient was operated on and recovered well. Nevertheless, a control angiog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

1997
1997
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Medical treatment is necessary for the underlying endocarditis and reduces the MA-related hemorrhagic risk (18). Some MAs may even resolve with antibiotic treatment (4,29,30). It can therefore be argued that EVT should be performed only after a full course of treatment with antibiotics.…”
Section: Evt Versus Medical Treatmentmentioning
confidence: 96%
“…Medical treatment is necessary for the underlying endocarditis and reduces the MA-related hemorrhagic risk (18). Some MAs may even resolve with antibiotic treatment (4,29,30). It can therefore be argued that EVT should be performed only after a full course of treatment with antibiotics.…”
Section: Evt Versus Medical Treatmentmentioning
confidence: 96%
“…In fact, septic aneurysms can form and rupture up to 6 to 9 months after eradication of the valvular source of emboli [19,20]. Despite the variability, many guidelines exist for management of these patients with antibiotics and followup angiograms [21][22][23], with intervals ranging from 1 to 3 weeks. Bingham [23] in 1977 concluded that there did not seem to be a clear advantage to surgery in addition to antibiotics, and recommended surgery after 6 weeks of antibiotics if the aneurysm did not reduce in size.…”
Section: Medicalmentioning
confidence: 98%
“…They occur in the setting of bacterial endocarditis, c o m p l i c a t i n g the m e d i c a l course of up to 25% of the patients affected with this disease [6,9,15,23,25,28,40]. N e urological manifestations of M A s can vary.…”
Section: Y C O T I C Aneurysms ( M Amentioning
confidence: 98%
“…represent 2% to 10% of all intracranial aneurysms [9,15,19,28]. They occur in the setting of bacterial endocarditis, c o m p l i c a t i n g the m e d i c a l course of up to 25% of the patients affected with this disease [6,9,15,23,25,28,40].…”
Section: Y C O T I C Aneurysms ( M Amentioning
confidence: 98%